Predicting Amazon Deforestation through the deterninants of demand for agricultural land - Andersen, Lykke E. (1996)
This paper develops a model of deforestation pressure in the Amazon. It is based on the determinants of demand for agricultural land, i.e. the interactions between population dynamics, urbanization and the growth of local markets, land prices, and government spending and policies. The mo deI is estimated using data from the period 1970 - 1985, and predictions for the period 1985 - 2010 are made under explicit assumptions about the underlying factors of deforestation. The predictions indicate that economic growth in the Amazon is likely to continue at high rates even if the federal government abandons its aggressive development policy. Deforestation will be much smaller if they do, though, since the active development policies tend to promote wasteful use of land.